2001
DOI: 10.1002/1097-4644(20010401)81:1<68::aid-jcb1024>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 (FGF-2) increases N-cadherin expression through protein kinase C and Src-kinase pathways in human calvaria osteoblasts

Abstract: Fibroblast growth factors (FGFs) are important factors regulating osteogenesis. However, the early mechanisms and signaling pathways involved in FGF actions in osteoblasts are unknown. We investigated the effects of FGF-2 on cell-cell adhesion and cadherin expression and the underlying signaling pathways in immortalized human neonatal calvaria (IHNC) cells. These cells express E- and N-cadherins, as shown by immunocytochemical and Western blot analyses. rhFGF-2 increased cell-cell adhesion at 24-72 h, as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 59 publications
4
48
1
Order By: Relevance
“…Involvement of a tyrosine kinase upstream of IKK activation has also been reported in CD23 signaling in U937 cells (32) and in Ag receptor stimulation in B cell (33). A similar PKC-dependent c-Src activation pathway has been found in human osteoblasts (36), in which fibroblast growth factor-2 increases N-cadherin expression; in A7r5 vascular smooth muscle cells (37), in which TPA induces Rho-dependent actin reorganization; and in SH-SY5Y neuroblastoma cells (38), in which TPA induces CasCrk complex formation. Furthermore, the PKC/c-Src/IKK pathway, in this study shown to be involved in induction of COX-2 expression, might be a common signaling pathway for inducible gene expression, as TNF-␣-, IL-1␤-, or IFN-␥-induced ICAM-1 expression in human alveolar epithelial cells also involves PKCdependent activation of c-Src or Lyn (26, 39 -41).…”
Section: Discussionmentioning
confidence: 52%
“…Involvement of a tyrosine kinase upstream of IKK activation has also been reported in CD23 signaling in U937 cells (32) and in Ag receptor stimulation in B cell (33). A similar PKC-dependent c-Src activation pathway has been found in human osteoblasts (36), in which fibroblast growth factor-2 increases N-cadherin expression; in A7r5 vascular smooth muscle cells (37), in which TPA induces Rho-dependent actin reorganization; and in SH-SY5Y neuroblastoma cells (38), in which TPA induces CasCrk complex formation. Furthermore, the PKC/c-Src/IKK pathway, in this study shown to be involved in induction of COX-2 expression, might be a common signaling pathway for inducible gene expression, as TNF-␣-, IL-1␤-, or IFN-␥-induced ICAM-1 expression in human alveolar epithelial cells also involves PKCdependent activation of c-Src or Lyn (26, 39 -41).…”
Section: Discussionmentioning
confidence: 52%
“…Functional interactions may also occur between PKC␣ and the tyrosine kinase Src (65,66). In osteoblasts, PKC␣ is known to activate Src signaling (67)(68)(69). However, we previously showed that MT FGFR2 reduces Src activity which thereby contributes to promote osteoblast differentiation (39).…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 and FGF18 stimulate ERK2 phosphorylation, which promotes mitogenesis (Hurley et al 1996;Chaudhary andAvioli 1997, 2000;Shimoaka et al 2001) and down-regulates procollagen gene expression in calvarial osteoblasts (Chaudhary andAvioli 1997, 2000). The protein kinase C (PKC) pathway is involved in the control of sodium-dependent phosphate transport (Suzuki et al 2000) and expression of N-cadherin in calvarial osteoblasts (Debiais et al 2001). Mutations in Fgfr2 that cause Apert syndrome induce constitutive activation of PKC in human calvarial osteoblasts (Fragale et al 1999;Lomri et al 2001).…”
Section: Fgf Signaling Pathways In Intramembranous Bone Formationmentioning
confidence: 99%
“…In human osteoblasts, Apert syndrome mutations do not increase cell proliferation (Lomri et al 1998;Fragale et al 1999;Lemonnier et al 2000) but alternatively, increase the expression of type 1 collagen, osteocalcin, and osteopontin, and enhance osteogenesis (Lomri et al 1998;Lemonnier et al 2000). This premature osteogenic cell differentiation induced by Apert Fgfr2 mutations is associated with increased N-cadherin expression and cell-cell adhesion (Lemonnier et al 2001b), which is reproduced by application of FGF2 (Debiais et al 2001). The increased osteoblast differentiation and bone formation induced by activating mutations in Fgfr2 is consistent with the phenotype of stenotic sutures in human nonsyndromic craniosynostosis (De Pollak et al 1996;Shevde et al 2001).…”
Section: Control Of Cranial Suture Closure By Fgf Signalingmentioning
confidence: 99%